Chemical composition and nutritive value of major available feed resources in three peasant associations of the Awassa Woreda - Alemayehu, Y.; Tegegne, Azage; Kurtu, M.Y. (Ethiopian Society of Animal Production, 2000)
A study was conducted in three peasant associations of the Awassa Woreda, southern Ethiopia for a period of one year (from June 1997 up to May 1998) with the objectives of determining the chemical composition and nutritive value of major feed resources. In the selection of three peasant associations, purposive sampling technique was used. While random sampling method was used in the selection, of 30 farmers per peasant association. Samples were collected for chemical composition and nutritional value analysis of those relatively major feed sources such as crop residues (maize stover, wheat straw, barley straw, and enset pseudo stems and. leaves), grazing pastures and trees/shrubs (A. albida and V. amygdalina). To determine the effect of season on chemical composition and nutritional value of natural grazing pastures and tree/shrub species, the year was divided into three seasons: June - August (medium rainfall season), September - November (big rainfall season) and December - May (Small rainfall season) based on the amount of rainfall distribution during the survey period. Samples of grazing pastures and tree species were collected throughout the year bulked by season and feed types and sub-samples were taken for laboratory analysis. However, samples of crop residues were collected in November when cereal crops were harvested. As a result, only one sub sample per crop residue was taken after being bulked of those samples collected from three peasant associations. The samples were analyzed for their DM, ash, CP, ADF, lignin, Ca, P and IVDMD values on dry matter bases. The ME was estimated from IVDMD values (ME in MJ = 0.17 * IVDMD % - 2.0). There was great variation in chemical composition and nutritional values between different available feed resources in the Woreda. Significant variation (p<0.05) was observed in DM and CP contents and (p<0.01) was observed in ash, ADF, lignin, Ca and P composition. However, seasonal effect was significant in ADF (p<0.05) and lignin (p<0.01) contents only.